Hypoxia Inducible Factors as Central Players in the Pathogenesis and Pathophysiology of Cardiovascular Diseases - Lucero García Rojas, Emilio Y.; Villanueva, Cleva; Bond, Richard A. (Frontiers in Cardiovascular Medicine, 2021)
Cardiovascular (CV) diseases are the major cause of death in industrialized countries. The main function of the CV system is to deliver nutrients and oxygen to all tissues. During most CV pathologies, oxygen and nutrient delivery is decreased or completely halted. Several mechanisms, including increased oxygen transport and delivery, as well as increased blood flow are triggered to compensate for the hypoxic state. If the compensatory mechanisms fail to sufficiently correct the hypoxia, irreversible damage can occur. Thus, hypoxia plays a central role in the pathogenesis and pathophysiology of CV diseases. Hypoxia inducible factors (HIFs) orchestrate the gene transcription for hundreds of proteins involved in erythropoiesis, glucose transport, angiogenesis, glycolytic metabolism, reactive o ROS handling, cell proliferation and survival, among others. The overall regulation of the expression of HIF-dependent genes depends on the severity, duration, and location of hypoxia. In the present review, common CV diseases were selected to illustrate that HIFs, and proteins derived directly or indirectly from their stabilization and activation, are related to the development and perpetuation of hypoxia in these pathologies. We further classify CV diseases into acute and chronic hypoxic states to better understand the temporal relevance of HIFs in the pathogenesis, disease progression and clinical outcomes of these diseases. We conclude that HIFs and their derived factors are fundamental in the genesis and progression of CV diseases. Understanding these mechanisms will lead to more effective treatment strategies leading to reduced morbidity and mortality.